If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(1 + 4d) = 19 (1 * -9 + 4d * -9) = 19 (-9 + -36d) = 19 Solving -9 + -36d = 19 Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -36d = 19 + 9 Combine like terms: -9 + 9 = 0 0 + -36d = 19 + 9 -36d = 19 + 9 Combine like terms: 19 + 9 = 28 -36d = 28 Divide each side by '-36'. d = -0.7777777778 Simplifying d = -0.7777777778
| -12x-3y=-12 | | 55=4w-13 | | 3f-11=4 | | -8+9c=19 | | 1/4x=24-1/2x | | 8+9c=19 | | 4/5X1/3= | | -12x-12x^2=0 | | (Z+2)(9x-5)=0 | | 12x+y=-3 | | 2b^2+5b-63=0 | | 261=79-x | | 1/x-1/x+1=1/x(2)+x | | 27-6z=-5(7z-9) | | X*2X=166 | | -16=4y-9 | | 2(8b+2)-1+4g-(2-5g)= | | -x-7=x+1 | | x=160-(170-x) | | 43=3u-11 | | x^3-12x^2-6x-12=0 | | 33b-23=b | | 29-5x=9-7x | | 12A-7=-1 | | y=0.15x+0.15 | | 7-4a=2a+2-5a | | 12=6-2y | | y-1=1/5(x-3) | | solvingx^3-12x^2-6x-12=0 | | -7-x=1+x | | -(7-7a)+4a=-23+3a | | 20x^2(-3+4x)=0 |